2019
DOI: 10.1111/epi.16381
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐term safety and efficacy of lacosamide and controlled‐release carbamazepine monotherapy in patients with newly diagnosed epilepsy

Abstract: Objective: A large-scale, double-blind trial (SP0993; NCT01243177) demonstrated that lacosamide was noninferior to controlled-release carbamazepine (carbamazepine-CR) in terms of efficacy, and well tolerated as first-line monotherapy in patients (≥16 years of age) with newly diagnosed epilepsy. We report primary safety outcomes from the double-blind extension of the noninferiority trial (SP0994; NCT01465997) and post hoc analyses of pooled long-term safety and efficacy data from both trials. Methods: Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…The overall percentage of patients reporting any TEAEs during the treatment period in SP1042 was lower in this open‐label trial (57.5%) versus the double‐blind (SP0993; 74%) 2 and double‐blind extension (SP0994; 64.9%) 8 trials. In this trial, 0.9% of patients discontinued due to TEAEs and 13.2% of patients reported serious TEAEs, which is lower or slightly higher, respectively, to rates observed in the double‐blind trials 2,8 .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The overall percentage of patients reporting any TEAEs during the treatment period in SP1042 was lower in this open‐label trial (57.5%) versus the double‐blind (SP0993; 74%) 2 and double‐blind extension (SP0994; 64.9%) 8 trials. In this trial, 0.9% of patients discontinued due to TEAEs and 13.2% of patients reported serious TEAEs, which is lower or slightly higher, respectively, to rates observed in the double‐blind trials 2,8 .…”
Section: Discussionmentioning
confidence: 61%
“…The overall percentage of patients reporting any TEAEs during the treatment period in SP1042 was lower in this open‐label trial (57.5%) versus the double‐blind (SP0993; 74%) 2 and double‐blind extension (SP0994; 64.9%) 8 trials. In this trial, 0.9% of patients discontinued due to TEAEs and 13.2% of patients reported serious TEAEs, which is lower or slightly higher, respectively, to rates observed in the double‐blind trials 2,8 . This may reflect an enriched population in the open‐label trial because patients who did not respond to lacosamide in the double‐blind trials, or who reported TEAEs leading to discontinuation, were not enrolled.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Lacosamide therefore could potentially have a narrower scope of antiseizure action, with less interference on normal bursts (especially those similar to seizure discharges, such as the repetitive rebound bursts in the cerebellar nuclear neurons triggered by the input from Purkinje neurons) 58 . This may partly explain why there is less ataxia and fewer relevant adverse events associated with lacosamide in clinical settings 59 . In‐depth considerations based on the molecular actions and therapeutic responses of ASDs are always advisable, and may in turn contribute to more pathophysiological understanding and a successful therapeutic regimen for each individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Hem etiyoloji; hem de LCM eklenme sırası ile ilgili olarak elde ettiğimiz bulgular literatür ile uyumlu görünmektedir. [17,11] Randomize kontrollü çalışmalarda LCM ile yan etki görülme sıklığı %37-43.3 arasında yayınlanmış; [15,21,22] azalan sıklıkta dizziness (sersemlik), uyku hali, çift görme, başağrısı ve kusma bildirilmiştir. [23] Bununla birlikte yan etki görülme oranlarının; idame fazında, titrasyon fazına kıyasla belirgin şekilde düştüğü de kaydedilmiştir.…”
Section: Discussionunclassified